Novel CFTR modulator combinations maximise rescue of G85E and N1303K in rectal organoids. Issue 2 (19th April 2022) - Ensinck, Marjolein M.; De Keersmaecker, Liesbeth; Ramalho, Anabela S.; Cuyx, Senne; Van Biervliet, Stephanie; Dupont, Lieven; Christ, Frauke; Debyser, Zeger; Vermeulen, François; Carlon, Marianne S.
Introduction: Cystic fibrosis (CF) is a severe monogenic disorder caused by mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. Several types of CFTR modulators (correctors/potentiators) have been developed to overcome protein dysfunction associated with these mutations. CFTR modulator therapy is now available for the major CF-causing mutations; however, 10% of people with CF remain without causal treatments. By combining investigational and market-approved CFTR modulators, we aimed to maximise functional rescue of iva-, luma- and tezacaftor refractory mutants G85E and N1303K. Methods: We used the well-established forskolin-induced swelling (FIS) in primary rectal organoids to assess responses to different CFTR corrector and potentiator types. The FIS analysis was performed with brightfield microscopy, allowing both 1-h and 24-h follow-up. Corrector and potentiator activity of elexacaftor was investigated. Results: For G85E, maximal rescue was observed by a combination of elexacaftor and corr4a. For N1303K, the quadruple combination teza-elexa-ivacaftor with apigenin was required to obtain a rescue similar to that of luma-ivacaftor rescued F508del. Elexacaftor rescued G85E and N1303K by different mechanisms, with chronic corrector effects on G85E and acute potentiation of N1303K only in the presence of ivacaftor. Synergy in N1303K rescue for iva-elexacaftor and apigenin suggests at least three potentiator mechanisms for this mutant. 24-h FIS identified ivacaftor as the main CFTR modulator for N1303K and elexacaftor and apigenin as co-potentiators. Conclusions: Novel combinations of CFTR modulators can further improve functional rescue of G85E and N1303K in rectal organoids, although for N1303K, more effective CFTR modulators are still needed. Organoids can guide personalised medicine in cystic fibrosis. Novel modulator combinations rescue G85E and N1303K beyond Trikafta. Label-free, long-term organoid monitoring unravels major contributors to the functional rescue of these rare CFTR mutants. https://bit.ly/3AKYJnz